100 plants to feed the bees : provide a healthy habitat to help pollinators thrive - Lee-Mader, Eric 1972-; Fowler, Jarrod; Vento, Jillian; Hopwood, Jennifer (Jennifer L.); Xerces Society (North Adams, MA : Storey Publishing, 2016)
The international bee crisis is threatening our global food supply, but this user-friendly field guide shows what you can do to help protect our pollinators. The Xerces Society for Invertebrate Conservation offers browsable profiles of 100 common flowers, herbs, shrubs, and trees that attract bees, butterflies, moths, and hummingbirds. The recommendations are simple: sow seeds for some plants--such as basil, rhododendron, and blueberries--and simply don't mow down abundant native species, including aster, goldenrod, and milkweed. 100 Plants to Feed the Bees will empower homeowners, landscapers, apartment dwellers--anyone with a scrap of yard or a window box--to protect our pollinators.
Preface: What's old is new -- Plants and pollinators : an overview -- Pollinators and pesticides -- Native wildflowers -- Native trees and shrubs -- Introduced trees and shrubs -- Introduced herbs and ornamentals -- Native and nonnative bee pasture plants -- Average number of flower and herb seeds per pound.
Includes index.
104886
Keywords: Pollination; Pollinators -- Conservation; Bees -- Conservation